From the earliest Gospel (Q+) to the Gospel of Mark : solving the synoptic problem with mimesis criticism /: solving the synoptic problem with mimesis criticism. (2019) - MacDonald, Dennis Ronald, 1946-; Van Dore, James R
No abstract available